Transformasi Komunikasi Dakwah Di Era Digital (Analisis Strategi dan Tantangan dalam Penyebaran Pesan Islami) - Wawan Sopiyan; Rahmat Ramdhani; Dede Sihabudin (STAI Bumi Silampari, 2025)
This study aims to explore the transformation of da'wah communication that occurs in the digital era, with a focus on analyzing strategies and challenges in spreading Islamic messages. The development of information and communication technology has driven a paradigm shift in the method of delivering da'wah. Digital media such as social media, blogs, and video platforms are now the main means used by da'i to reach a wider audience, especially the younger generation who are very familiar with the digital world. The research method used is qualitative with a case study approach and content analysis, and is complemented by in-depth interviews with da'wah practitioners and analysis of relevant literature. The results of the study show that transformation through digital media opens up significant opportunities to increase the reach and interactivity of da'wah message delivery. However, there are also a number of challenges, including difficulties in maintaining message authenticity, content verification, and data security and privacy issues. In addition, competition with a flood of information from various digital sources also forces da'wah practitioners to develop innovative and adaptive communication strategies so that Islamic messages continue to be conveyed effectively and on target. The findings of this study are expected to provide strategic recommendations for religious institutions in optimizing the use of digital technology for the dissemination of da'wah messages, as well as offering solutions to the challenges that arise. This research also contributes to the development of modern da'wah methodology that is relevant to the dynamics of the digital era, so that it is expected to be able to maintain the sustainability and attractiveness of Islamic values ??in a global context.